Indonesia Public Libraries in the Age of AI Disruption: Building Dynamic Capabilities - Srirahayu, Dyah Puspitasari; Anugrah, Esti Putri (Program Studi Ilmu Perpustakaan UIN Alauddin, 2026)
Background: The disruption caused by artificial intelligence (AI) extends beyond profit-oriented sectors, fundamentally altering the operational landscape of non-profit institutions, including public libraries. To navigate this volatile environment, libraries must leverage Dynamic Capabilities (DC), the ability to integrate, build, and reconfigure internal and external competences to address rapidly changing environments. Purpose: This study explores how public libraries in Indonesia develop and deploy dynamic capabilities to address the challenges and opportunities presented by AI disruption. Methods: Adopting a multiple-case study design, research was conducted across seven public libraries in East Java (East Java Provincial, Malang, Jember, Probolinggo, Tulungagung, Pamekasan, and Kediri). Data were gathered through semi-structured interviews with 14 key informants, including library directors and senior librarians, to capture a comprehensive view of institutional responses. Findings: The study indicates that Indonesian public libraries have successfully activated Sensing capabilities to detect AI-related threats and shifts. Furthermore, these institutions demonstrated diverse Seizing capabilities through creative and adaptive strategic responses. Finally, Transforming capabilities were evidenced through structural organizational reconfiguration, human resource capacity building, strategic budget reallocation, and the reformulation of institutional policies. Originality/Value: This study provides empirical evidence that the Dynamic Capabilities framework is a vital tool for non-profit survival in the AI era. It offers a blueprint for library administrators to move beyond traditional roles, emphasizing that institutional agility and policy flexibility are essential for maintaining relevance in a digitally disrupted society.